IN VITRO GROWTH RATE OF Kappaphycus alvarezii MICROPROPAGULE AND EMBRYO BY ENRICHMENT MEDIUM WITH SEAWEED EXTRACT - Emma Suryati; Rosmiati Rosmiati; Andi Parenrengi; Andi Tenriulo (Indonesian Aquaculture Journal, 2015)
The development of micropropagule and embryo of seaweed depend on nutrient and fertilizer used. Seaweed has been reported contain hormone regulators such as auxine, cytokinine, gibbereline, and various minerals applied in stimulating the growth ocra plant and wheat culture. The objectives of this study were to determine the potential of Kappaphycus alvarezii extract and its optimal concentration in accelerating of Kappaphycus alvarezii micropropagule and embryo growth. Micropropagule and embryo produced through callus induction were planted into PES 1/20 liquid medium supplemented with seaweed extract at the concentrations of 0 (control), 25, 50, 75, and 100 μL in 10 mL of medium. The results showed that medium enrichment with 50 μL of seaweed extract had the highest survival rate and growth of thallus. In addition, this concentration was also resulted in a good performance of K. alvarezii thallus with the lighter color. The advantage of this study for seaweed cultivation in Indonesia, among others, seaweed can be used as fertilizer, especially in the maintenance of seaweed seed, so that cultivation can be better develop.